Born global companies. Is this a future for economy of Latvia? A preliminary study - Vaivode, Irena (Business: Theory and Practice, 2018)
A small number of export-capable sectors is a factor that renders the Latvian economy sensitive to any changes in the external environment, at the same time it is an incentive to look for growth patterns. Internationalisation is a factor that brings growth. International operations can have various advantages for enterprises, particularly for high-growing companies. The born global companies will experience stronger performance in markets that are more attractive and more internationalised. For this research purposes term ‘born global’ author understands as a ‘truly global’ company as well as domestically based company with overseas operations. The novelty of the research manifests as seeking of novel information and novel solutions based on the experience of different countries. Born global companies are the research object of an investigation. The aim of the article is an analysis of external environment perspective that is necessary to predict long-term survival for every company in conjunction with economic dimensions of globalization. The research methodology is based on the overview of literature sources that attempts to describe the key drivers for early internationalization, statistics of high-growth enterprises and survival rates of newly born enterprises, success factors of high-growth enterprises. As the result framework for the future research is created.